Mathematical model of chip serration frequency in end milling of Inconel 718 - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Ishtiyaq, M. H. (2008)
Chip morphology under different cutting conditions is different. Serious vibrations are often encountered due to chip segmentation that limits material removal rates. In order to increase productivity, tool life and chatter suppression in the machining of Inconel 718, it is necessary to study the chip segmentation phenomena and its influencing factors. It has been identified that the chip formation process has a discrete nature, associated with the periodic shearing process of the chip during machining of Inconel 718. Apart from the primary serrated teeth, a typical instability of periodic nature, in the form of secondary saw/serrated teeth, which appear at the free edge of the chip, has been identified. Mechanism of formation of these teeth has been studied and the frequency of their formation has been determined. In this paper a new interpretation of chip serration frequency in end milling of Inconel 718 using TiAlN insert under dry condition is presented in terms of cutting parameters. On the basis of these interpretations, a new analytical model is proposed to predict the frequency of chip serration frequency by response surface methodology and the effects of different cutting parameters on chip serration frequency were investigated both experimentally and numerically.